Protein S deficiency complicated pregnancy in women with recurrent pregnancy loss - Shinozaki, Nanae; Ebina, Yasuhiko; Deguchi, Masashi; Tanimura, Kenji; Morizane, Mayumi; Yamada, Hideto (Gynecological endocrinology, 2016)
This prospective study aimed to evaluate pregnancy outcome and complications in women with recurrent pregnancy loss (RPL) and protein S (PS) deficiency, who received low dose aspirin (LDA) or LDA plus heparin (LDA/H) therapies. Clinical characteristics, pregnancy outcome and complications of 38 women with two or more RPL and <60% of plasma free PS antigen were compared among three groups: antiphospholipid antibody (aPL)-negative women who received LDA (group A), aPL-negative women who received LDA/H (group B) and aPL-positive women who received LDA/H (group C). Gestational weeks (GW) at delivery in group C (median 32 GW) were earlier than 40 GW in group A and 38.5 GW in group B (p < 0.05). The birth weight in group C (median 1794 g) was less than 2855 g in group B (p < 0.05). The incidences of fetal growth restriction (37.5%), pregnancy-induced hypertension (37.5%), and preterm delivery (62.5%) in group C were higher than those (4.5%, 0%, and 4.5%, respectively) in group B (p<0.05). Women with RPL, PS deficiency, and positive aPL had high risks for adverse pregnancy outcome and complications, even when they received LDA/H therapy. Among women with RPL, PS, and negative aPL, there was no difference in these risks between LDA alone and LDA/H therapies.